MENCAPAI KEBERMAKNAAN HIDUP PENDERITA CACAT MELALUI AKTIVITAS JASMANI - Komarudin Komarudin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
Achieving a meaningful of life in broader terms can be defined as human efforts to actualize themselves, in order to gain confession in their environment freely without separated by social structures which is becoming human rights. Disability person caused by congenital factors or the effect from an incident which resulted disability is also a part of the society who have equal rights to improve the meaning of life in the social environment. Physical activity is one of the appropriate tool for disability people to actualize theirself. By doing physical activity, people with disablities are able to socialize, improve their self- confidence an also learn the value of tolerance, cooperation, sportsmanship as a moral attitude that is necessary to being a part of the social environment. The form of physical activity should be appropriate. The appropriate form of physical activity will allows disability people to perform unhampered, therapy and rehabilitation to generate a belief that they can raise the meaning of their life even having physical limitations. Keywords: The meaningful of life, Disability, Physical activity